Anterior mediastinotomy. Issue 4 (July 1973) - Evans, D. S.; Hall, J. H.; Harrison, G. Kent
Abstract : The indications and techniques for performing the operation of anterior mediastinotomy are described. In the years 1966-71, 116 anterior mediastinotomies were done. The results of these are presented. In 36 patients the operation was done to provide a histological diagnosis in benign conditions. In 51 patients, with probable carcinoma but normal bronchoscopy, mediastinotomy was done to establish a diagnosis and assess operability; 43 had involved mediastinal nodes proven on histology. In a further 29 patients, with positive bronchoscopic biopsies, mediastinotomy was done to assess operability alone. In all, 14 patients (17·5%) were judged suitable for thoracotomy. Of these, nine had operable disease while five were found to be inoperable. The incidence of complications of the operation was low (11%). These were mostly minor, There were no deaths. Most patients, after anterior mediastinotomy alone, were fit for discharge 48 to 72 hours after the operation. The value of an operation that provides both diagnosis and assessment of mediastinum, lung, and pleura is discussed. The operation of anterior mediastinotomy is compared with mediastinoscopy and, in our opinion, the superiority of the former is demonstrated.